2016
DOI: 10.11648/j.ajss.20160402.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Muscle Energy Technique in Increasing Range of Motion and Strength of Glenohumeral Internal Rotator, in Athletes with Glenohumeral Internal Rotation Deficit

Abstract: Abstract:Study design: Randomized control trial. Objective: To measure the effect muscle energy technique(MET) for the glenohumeral joint external rotators to improve the range of motion and strength of internal rotators in athletes with glenohumeral internal rotation deficit (GIRD). Background: Glenohumeral internal rotation deficit is one of the leading causes of impairments in overhead throwing athletes. Anatomical GIRD is though considered to be normal in overhead athletes but it may further lead to osseou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Previous studies showed that restricted SUR is linked to IR ROM limitation, such as glenohumeral internal rotation deficit [ 36 , 37 ]. In addition, the ROM and strength of IR in the throwing shoulder are limited due to osseous adaptation, posterior muscle tightness and posterior inferior capsule tightness [ 38 ]. This is also caused by weakness of the rotator muscle and variations in scapula-humeral rotations (dyskinesis) [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that restricted SUR is linked to IR ROM limitation, such as glenohumeral internal rotation deficit [ 36 , 37 ]. In addition, the ROM and strength of IR in the throwing shoulder are limited due to osseous adaptation, posterior muscle tightness and posterior inferior capsule tightness [ 38 ]. This is also caused by weakness of the rotator muscle and variations in scapula-humeral rotations (dyskinesis) [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quando a mão do participante tocava a espinha ilíaca ântero-superior, ela voltava lentamente à posição inicial, girando externamente, estendendo-se horizontalmente e abduzindo o úmero. 18 Os exercícios de fortalecimento envolveram sessões de supervisão do fisioterapeuta com 12 repetições e três séries cinco dias por semana até oito semanas.…”
Section: Procedimentos Fortalecimento Dos Músculos Rotadores Internos...unclassified
“…O alongamento foi mantido por 10 segundos, 12 repetições e 3 séries 5 dias por semana até oito semanas. 18…”
Section: Técnica De Energia Muscular Do Rotador Externo Do Ombro (Tem)unclassified
“…Finally, Grade III force provides enough diversion or glide to allow the joint capsule to fully stretch; it is frequently utilised [1]. Muscle energy techniques are a subset of soft tissue osteopathic (originally) manipulation techniques that include patientspecific, precisely guided and controlled manipulation, as well as patient-initiated isometric and/or isotonic contractions, all aimed at improving musculoskeletal function and pain relief [13]. Muscle energy techniques (MET) extend muscles by combining mechanical and plastic changes in connective tissue.…”
Section: Introductionmentioning
confidence: 99%